2009
DOI: 10.1007/s00404-009-1165-2
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic-peritoneal tuberculosis simulating peritoneal carcinomatosis: high clinical suspicion and a minimally invasive procedure

Abstract: Peritoneal tuberculosis (TB) is still a major health problem in developing countries. We describe a 26-year-old woman with peritoneal TB presenting with lower abdominal pain and distention, weight loss, and night sweats. There are no pathognomonic clinical, laboratory, or radiologic findings for peritoneal TB. Therefore, it can be easily confused with peritoneal carcinomatosis and advanced ovarian carcinoma. Adenosine deaminase activity in ascitic fluid combined with a high clinic suspicion is an effective and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…In another study showed that ADA activity is important for differentiating tuberculosis from malignant pleural effusions [23]. In gynecology, peritoneal fluid ADA activities have been found to be useful in differentiating peritoneal TB and ovarian cancer [7][8][9]24]. In daily practice, peritoneal TB can be easily confused with peritoneal carcinomatosis and advanced ovarian carcinoma.…”
Section: Discussionmentioning
confidence: 94%
“…In another study showed that ADA activity is important for differentiating tuberculosis from malignant pleural effusions [23]. In gynecology, peritoneal fluid ADA activities have been found to be useful in differentiating peritoneal TB and ovarian cancer [7][8][9]24]. In daily practice, peritoneal TB can be easily confused with peritoneal carcinomatosis and advanced ovarian carcinoma.…”
Section: Discussionmentioning
confidence: 94%
“…The findings of pelvic and/or omental mass, ascites, and elevated CA-125 have been described as a presentation of pelvic TB (19). Thus, reproductive-aged women with identifiable risk factors for TB should have genital TB in the differential diagnosis.…”
Section: Discussionmentioning
confidence: 98%
“…CA-125, the common tumor marker of ovarian cancer, is also elevated in patients with pulmonary and extrapulmonary tuberculosis. 5 This is because CA-125 antigen is a large transmembrane glycoprotein derived from coelomic and mullerian epithelium. Elevation of CA 125 antigen can be caused by ovarian cancer and other malignancies.…”
Section: Discussionmentioning
confidence: 99%